Avaliação das políticas de inclusão na Universidade Federal do Ceará: políticas de ingresso e permanência para estudantes “cotistas” - Menezes Neto, José Alty de (2020)
This master's thesis, entitled Public Inclusion Policies Evaluation in UFC: policies of entrance and permanence for "quota students", it was made in order to assess the quota policies and student's support, from the both programs benefited individual's perspective. Especifically, the purpose is ponder about the entrance of quota students in UFC, arguing the role of Student Welfare. For this purpose, we chose two graduation courses in the educational institution: Architecture and Pedagogy. For the execution of this research object, it had to be made a study of racial-ethnic relations and historical-social construction of the brazilian society. We took up for a paradigm which works in a counter-hegemonic evaluation, which had been inspired in Lea Carvalho Rodrigue's Profundity Evaluation, however, without the purpose to attend for the four evaluative axles wrote by the author, besides that, we use the quantitative and qualitative research principles. To make this research happen, it has been used laws and federal decrees, Education Ministry's database, literature search and interviews made with open questions applied to the students from the courses of which this research take up. The results showed that, even though the UFC had been applied the quotas program before the deadline and the financial resources had been passed on, year on year, for the Students support, is unsettling the quota student's situation. There are various student´s socio-economic profiles, with the student from pedagogy course in a higher vulnerable situation. In both cases, more in Architecture than in Pedagogy, discrimination were reported. There are many testimony which shine through the social segregation in personal relationships and unequal professor´s treatment. We verified that exists a veiled discrimination, which have never been discussed, against the quote students in academic background. Furthermore, students have an unfavourable opinion about Student Welfare. In fact, even though the big importance of a student welfare program, many students reported problems with the subsides, criticizing, the bureaucratic condition.